2018
DOI: 10.1038/s41598-018-24591-w
|View full text |Cite
|
Sign up to set email alerts
|

A new family of periplasmic-binding proteins that sense arsenic oxyanions

Abstract: Arsenic contamination of drinking water affects more than 140 million people worldwide. While toxic to humans, inorganic forms of arsenic (arsenite and arsenate), can be used as energy sources for microbial respiration. AioX and its orthologues (ArxX and ArrX) represent the first members of a new sub-family of periplasmic-binding proteins that serve as the first component of a signal transduction system, that’s role is to positively regulate expression of arsenic metabolism enzymes. As determined by X-ray crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 51 publications
1
22
0
1
Order By: Relevance
“…The arxXSR genes are absent from the arx gene cluster of the genomes from members of the order Oceanospirillales (Figure 4). Similar findings were reported in previous studies on the gene clusters of aio and arr , which indicated that the presence of aioXSR and arrXSR is variable among taxonomic groups (Slyemi and Bonnefoy, 2012; Van Lis et al, 2013; Badilla et al, 2018). The aioXSR genes regulate the expression of the aioAB genes in some arsenite-oxidizing strains (Kashyap et al, 2006; Koechler et al, 2010; Sardiwal et al, 2010; Liu et al, 2012; Li et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The arxXSR genes are absent from the arx gene cluster of the genomes from members of the order Oceanospirillales (Figure 4). Similar findings were reported in previous studies on the gene clusters of aio and arr , which indicated that the presence of aioXSR and arrXSR is variable among taxonomic groups (Slyemi and Bonnefoy, 2012; Van Lis et al, 2013; Badilla et al, 2018). The aioXSR genes regulate the expression of the aioAB genes in some arsenite-oxidizing strains (Kashyap et al, 2006; Koechler et al, 2010; Sardiwal et al, 2010; Liu et al, 2012; Li et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…Comparison among amino acid sequences of the ArxAB encoded in the identified genomes indicated that they share some characteristics with those of A. ehrlichii MLHE-1 and Ectothiorhodospira sp. PHS-1 reported in previous studies (Zargar et al, 2010, 2012; Van Lis et al, 2013; Badilla et al, 2018), as described below. The ArxA sequences had three conserved regions commonly identified in subunit A of the DMSO reductase family enzymes: an iron–sulfur [4Fe-4S] motif; a catalytic binding pocket sequence similar to that suggested in the ArxA of A. ehrlichii MLHE-1 and Ectothiorhodospira sp.…”
Section: Resultsmentioning
confidence: 99%
“…It is assumed that the regulator AioR does not interact directly with arsenite, is one component of the signal transduction that involves AioX that binds arsenite at periplasm, and the histidine-kinase AioS that transfer the information from the periplasm to the cytoplasm (Kashyap et al, 2006; Saltikov, 2011). It is possible that this scheme is also present in CIB strain with the component of the arx cluster, being ArxX protein the periplasmic arsenite binding protein (Badilla et al, 2018), ArxS the sensor kinase responsible for the information transduction to the cytoplasm, and ArxR the response regulator that sense the signal transferred by ArxS. Further experiments about this subject are required to establish the complete network of regulation of the arx genes in Azoarcus sp.…”
Section: Resultsmentioning
confidence: 99%
“…Crucially, the binding of AsO4 3to the AioX protein and AsO3 3to the ArrX protein could not be detected 46 , indicating significant specificity of these two PBPs for their respective substrates.…”
Section: Introductionmentioning
confidence: 93%